Political Crises, Democratic Backsliding and SDGS in Tunisia: Challenges, Implications, and Pathways to Progress - Khammassi, Soumaya (Journal of Posthumanism, 2025)
This study investigates the complex relationship between political crises, democratic backsliding, and sustainable development in post-revolution Tunisia. Politics in Tunisia has maintained an active movement between democratic progress and institutionally fragile periods since 2011. The 2019 presidential victory of Kais Saied became the starting point for authoritarian power consolidation into 2021 that caused damage to institutions, reduced civil freedoms, and extended socio-economic problems. The study goes into great detail about how the current political unrest slows down progress on important Sustainable Development Goals (SDGs), such as SDGs 8 (Decent Work), 10 (Reduced Inequalities), 11 (Sustainable Cities), 12 (Responsible Consumption), and 16 (Peace and Justice). A mixed-methods approach is used to combine SDG Index data with economic data and feedback from Arab Barometer Wave VIII participants and Wave VII survey respondents. The indicators we looked at show that a loss of democracy has negative effects on development. For example, unemployment rises, public trust falls, and decentralization slows down. At the same time, environmental governance falls. The report also outlines potential choices for turning the trend around, including domestic institutional reform, international cooperation, civil society action, and policy designs grounded in international best practices. The study ends by emphasizing that despite the ongoing political uncertainty, Tunisia is still able to catch up with sustainable development through participatory, transparent, and evidence-based governance.